MANAJEMEN RETRIBUSI PASAR MANONDA DI KOTA PALU - Septiani, Indah (Katalogis, 2018)
To know management of market levy manonda in Palu City if seen three indicator from four indicator of management function according to George R. Terry. The data used in this study are primary data and secondary data obtained by observation data and in-depth interviews. The method used in this research is qualitative method with the determination of informant using purposive technique. As for research technique using interactive model. Based on four indicators of research that is planning, organizing, moving indicate in execution of manonda market retribution management in Palu City, not yet running maximally, where indicator of planning and supervision not yet run properly, Due to the determination of retribution target still not running in accordance with the expectation that the target market levy manonda in Palu city that should be able to reach Â± Rp. 1.544.400.000 But only determined Rp. 748.800.000 in 2017. As well as obstacles from supervisory indicators are still lack of data collection of traders and carcin that is routinely implemented which should be carcin data collection can be done every month so that supervision function can be optimal. The other two indicators have proceeded in accordance with expectations where for the organizing indicators with the grouping of officers and the division of labor done well by the market field then this indicator can run well and the indicator of the movement with the head of market and head of market routine to go to the field directly and Giving directions every day makes this mobilization function optimal.